IVF AND CHILDLESSNESS IN BANGLADESH - TASLIMA SULTANA, MIRZA. (ABINGDON)
1 online resource
Keywords: This book examines motherhood and childlessness within the context of the emergence of In Vitro Fertilization (IVF) in Bangladesh. It studies the development of IVF procedures through a socio-economic and historical lens. The author delves into policy issues, the media representations of IVF, IVF advertisements, and looks at IVF clinics as sites for commercializing the hope of childless people. The book addresses the lack of regulation surrounding IVF procedures. It brings to the fore the dynamics of reproductive restraint and choice, as well as patterns of gender empowerment and control, which are at play within the norms, practices, and dynamics of Bangladeshi identities.Rich in ethnographic case studies, this book will be indispensable for scholars and researchers of public health, women's health, gender studies, women's studies, science and technology studies, sociology, medical anthropology, public policy, and South Asian studies.